The Evaluation of Public Relations in the Era of Fake News: Examination of How the Rise of Misinformation Has Changed Public Relations Practices in Nigeria - Heavens Ugochukwu Obasi (International Journal of Education, Culture, and Society, 2026)
The proliferation of fake news, particularly through social media, has significantly reshaped public relations practice by challenging organizational credibility, reputation, and stakeholder communication in Nigeria. This study examined public relations in the era of fake news, with specific focus on how misinformation affects public relations practice in Aba, Abia State. The study was motivated by the growing influence of false information on public perception and its disruptive effects on relationships between organizations and their stakeholders. A descriptive survey design was adopted, and data were collected through a structured questionnaire administered to 100 respondents drawn from a population of 150 using the Yaro Yamane formula. Responses were measured and analyzed using a Likert scale. The study sought to determine the impact of fake news on public relations practice and reputation management, identify the strategies used by public relations practitioners to detect and counter misinformation, assess the effectiveness of these strategies, and highlight the challenges associated with addressing misinformation in Nigeria. The findings revealed that fake news significantly undermines public relations practice by contributing to loss of public trust, reputational crises, and misinformation-driven conflicts. Public relations practitioners were found to rely primarily on media monitoring, fact-checking, press releases, and social media engagement to manage misinformation. However, the effectiveness of these strategies remains constrained by inadequate digital monitoring tools, low public media literacy, and weak regulatory frameworks. The study concludes that fake news poses a serious threat to the integrity and operational effectiveness of public relations in Nigeria. It contributes to the growing discourse on strategic communication by underscoring the need for digital verification tools, collaboration with media organizations, proactive crisis communication frameworks, media literacy campaigns, capacity building, and stronger regulatory mechanisms to improve information credibility and strengthen public trust in organizational communication.